(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
Gender roles determine the expected behavior of men and women in certain situations and play a significant role in culture and society. However, the problem of gender inequality is that these roles and expectations can lead to limitations in people’s capabilities, behavior and identity. For example, stereotypes can lead to discrimination against women at work or to inequality of opportunities in the field of sports. Currently, there is a need for a radical reorganization of physical education, changing views on physical culture and sport and physical education in general, and even reviewing the methodology of physical education in higher education institutions. The problems of organizing physical education require a comprehensive approach. In the modern world, physical education and sports play an important role in the formation of a harmoniously developed personality, contributing not only to the physical, but also to the social, moral and psychological development of a person. However, the issues of integrating a gender approach into this area remain extremely relevant, because traditional stereotypes and unequal opportunities still significantly affect access to sports resources, teaching methods and the choice of disciplines. When organizing educational and practical classes in physical education, classes must necessarily be built taking into account gender characteristics. The gender approach in physical education and sports is designed to take into account the biological, social and cultural characteristics of representatives of different sexes, creating conditions for the equal development of their potential. At the same time, it faces a number of challenges, such as the persistence of stereotypes, insufficient understanding of gender aspects among teachers and coaches, as well as the need to adapt educational programs to modern realities. This article is devoted to the analysis of the main problems, experience in implementing a gender approach, and prospects for its development in the field of sports and physical education, with the aim of emphasizing the importance of equality and inclusion for modern society.